การแปลนวนิยายเรื่อง True History of the Kelly Gang ของ Peter Carey - ธัชรุจี เคาวสุต (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This special research aims to study the translation approaches, problems and solution in translating True History of the Kelly Gang, a fiction written by Peter Carey, whose main character uses unique writing style. The researcher selected chapter 1 as the case study for this research. The theories and concepts used as framework to translate and to solve the problems in translating this fiction include Discourse Analysis, Interpretative Theory, Fortunato Israël’s literary translation concepts, and Sociolinguistics. Having followed the theoretical frameworks mentioned above, the researcher found that in order to understand the source text profoundly and to render proper translation, the translator had to analyze the source text thoroughly. In addition, the translator needs to make decisions on several key issues, namely, type of translation, pronouns for the characters, language register, and word selection in order to give equivalence in meaning and to maintain the author’s style.